The influence of ASCE 7–16 wind load provisions on a vulnerability model of Florida residential construction - Bedwell, Christian; Gurley, Kurtis; Pinelli, Jean-Paul; Silva de Abreu, Roberto Vicente (Frontiers in Built Environment, 2022)
The Florida Public Hurricane Loss Model (FPHLM) is a probabilistic risk model designed to estimate wind induced insurance losses to residential infrastructure in Florida. In the physical damage estimation module, Monte Carlo simulation is employed to generate damage matrices as a function of wind speed by comparing probabilistic building component capacities to wind loads. These damage matrices are input to a repair cost algorithm, ultimately producing damage ratios as a function of wind speed for different building classes. It is required that the inventory of residential building models reflect the history of construction practice within Florida. Differing eras of construction are represented by developing component-wise options for probabilistic capacities and load paths, resulting in a suite of hundreds of model variants. Regarding loads, the probabilistic wind load model is based on a directionalized adaptation of ASCE 7, and its representation in the model is kept current with the version adopted by the Florida Building Code (FBC). In 2020 the FBC adopted by reference ASCE 7-16, which contains important changes to the wind-load provisions. These changes have implications for both the loading and resistance aspects of the physical damage model, thus influencing insured loss projections. This study discusses the development and implementation of these changes within the model and investigates the impacts on the modeled vulnerability of residential structures in Florida. Comparing vulnerability estimates of structures designed before and after the FBC adoption of ASCE 7-16 provide insight into the potential effectiveness of such changes to improve community resilience.